Kontribusi Perpustakaan Sekolah Terhadap Peningkatan Literasi Membaca Siswa Kelas IV Sekolah Dasar - Afrilia, Resti; Sulaeman (University of Muhammadiyah Malang, 2024)
The decline in reading interest hinders the quality of student learning, reducing reading literacy skills. In education, reading is a mandatory activity for students. The presence of a school library can help improve students' reading literacy and support the teaching and learning process. A library serves not only as an information source but also as a learning facility that supports the achievement of educational goals. To meet these goals, school libraries must be developed in terms of management, collection, and facilities to enhance students' reading literacy. This research aims to explore the importance of libraries in improving the reading literacy of fourth-grade elementary school students and to assess the library's contribution to enhancing their reading literacy. The study employs a descriptive qualitative method, using observation, interviews, and documentation techniques, involving the principal, one second-grade teacher, the fourth-grade homeroom teacher, and five fourth-grade students. The findings indicate that the school library contributes effectively by improving reading literacy and supporting the teaching and learning process, thus enhancing student learning outcomes. A well-equipped school library, with easy access, engaging literacy activities, proactive librarian roles, and stakeholder collaboration, can significantly improve students' reading literacy. Students involved in various literacy activities tend to have a high interest in reading, leading to improved reading skills and comprehension. A well-managed library becomes a literacy center supporting students' academic success and development.